Yield of different rice cultivars at two levels of soil salinity under seawater intrusion in West Java, Indonesia - Nuning Argo Subekti; Hasil Sembiring; Erythrina; Dedi Nugraha; Bhakti Priatmojo; Nafisah (Society for Indonesian Biodiversity, 2020)
Abstract. Subekti NA, Sembiring H, Erythrina, Nugraha D, Priatmojo B, Nafisah. 2020. Yield of different rice cultivars at two levels of soil salinity under seawater intrusion in West Java, Indonesia. Biodiversitas 21: 14-20. A tendency to use saline water in rice production is rising in recent years, but the adaptation of variety under saline conditions is still questionable. The aim of the study was to evaluate the response of several rice cultivars on the growth and yield of rice under seawater intrusion in West Java. Two salt-tolerant cultivars (Inpari 34 and Inpari 35), two promising lines (PL-1 and PL-2) and two modern cultivars (Inpari 30 (Ciherang sub1) and Sidenuk) were evaluated in two soil salinity levels. In each farmer's field a Randomized Complete Block Design was applied with three replications per treatment. Results showed that Sidenuk and Inpari 30 produced same yield compared to tolerant varieties and promising lines during dry season under moderate soil salinity. There were not much different among the cultivars tested in terms of plant height and tiller number as well as the biomass and harvest index. However, under high soil salinity seed germination, plant height, number of tillers per plant, above-ground biomass, spikelet number, percent of sterile florets and productivity were significantly affected. Saline tolerant varieties Inpari 34 and Inpari 35 showed their superiority compared to non-tolerant varieties. Both varieties produced 40% higher yield than Inpari 30 (Ciherang sub 1) and Sidenuk.